DEVELOPMENT OF INSECT-RESISTANT COTTON LINES WITH TARGETED EXPRESSION OF INSECTICIDAL GENE - Bakhsh, Allah; Anayol, Emine; Khabbazi, Saber Delpasand; Karakoç, Ömer Cem; Sancak, Cengiz; Özcan, Sebahattin (Archives of Biological Sciences, 2016)
In order to address biosafety concerns regarding the constitutive expression of foreign genes in crops, we applied a strategy aimed at confining foreign gene expression in insect wounding sites of cotton. For this purpose, a plant expression construct was designed by cloning the AoPR1 promoter (pathogenesis-related protein gene isolated from Asparagus officinalis) upstream from the insecticidal gene cry1Ac. The Turkish cotton cultivar cv. STN-468 was transformed using the Agrobacterium tumefaciens strain LBA4404 containing the recombinant binary vector pRD400 harboring cry1Ac under a wound-inducible promoter. The neomycin phosphotransferase (nptII) gene was used as a selectable marker at a concentration of 100 mg/L. The primary transformants were analyzed for T-DNA integration and expression using standard molecular approaches. The efficacy of insecticidal gene control of the AoPR1 promoter was investigated using leaf bioassays with 2nd instar larvae of Helicoverpa armigera and Spodoptera littoralis. Positive primary transformants from T0 progeny were further raised under greenhouse conditions to obtain progeny (T1). The introduced gene was properly inherited and expressed in T1 progeny. The mechanical wounding of plants resulted in increased cry1Ac protein levels during 0-48 h of the wounding period. The transgenic lines exhibited appreciable levels of resistance against targeted insect pests in the leaf bioassays. The use of a wound-inducible promoter to drive insecticidal gene expression is a valuable insect resistant management strategy as gene expression will remain limited to the insect biting sites of plant and crop, food and environmental concerns can be minimized. DOI: 10.2298/ABS151012063B Key words: cotton modification; cry toxin; confined expression; insecticidal gene Accepted: October 12, 2015; Revised: October 27, 2015; Accepted: November 4, 2015; Published online: August 2, 2016 How to cite this article: Bakhsh A, Anayol E, Khabbazi SD, Karakoç ÖC, Sancak C, Özcan S. Development of insect-resistant cotton lines with targeted expression of insecticidal gene. Arch Biol Sci. 2016;68(4):773-80.